ANALISIS ZAT HIDROQUINON PADA KRIM PEMUTIH WAJAH YANG BEREDAR DI KOTA MANADO - Prabawati, I Dewa Ayu; Fatimawali, Fatimawali; Yudistira, Adithya (PHARMACON, 2012)
Cosmetic whitening is a cosmetic that contains the active ingredient intended to bleach and brightenthe skin or whiten the skin. Hydroquinone is used in bleaching creams but is prohibited because it cancause skin irritation, skin redness and burning, and can also cause abnormalities in the kidneys, bloodcell cancer, and liver cancer. The purpose of this study is to prove the presence or absencehydroquinone content in various brands of whitening creams circulating in the city of Manado. Bleachcream samples studied were sample A, sample B, sample C, and sample D. The content ofhydroquinone was observed using the method of thin layer chromatography and UVspectrophotometer. The results showed that the four samples, namely Kelly, Quina, Fair Check, andOriens, the hydroquinone was not identified, either using thin layer chromatography or UVspectrophotometer. Thus it is certain that the four facial bleaching cream products are free fromhydroquinone.Key words : Hydroquinone, Cosmetic whitening, Layer Chromatography (TLC),UV spectrophotometer